2010
DOI: 10.1111/j.1463-6395.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of spermiogenesis in the Jamaican Gray Anole, Anolis lineatopus (Reptilia: Polychrotidae)

Abstract: Rheubert, J.L., Wilson, B.S., Wolf, K.W. and Gribbins, K.M. 2010. Ultrastructural study of spermiogenesis in the Jamaican Gray Anole, Anolis lineatopus (Reptilia: Polychrotidae). -Acta Zoologica (Stockholm) 91: 484-494.As the number of spermatozoal characters being described in reptiles increases, it is important to detail the ontogeny of the features leading to the mature morphology of the spermatozoa which may give rise to more comprehensive data matrices for future phylogenetic analyses within the Reptilia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 33 publications
5
27
1
Order By: Relevance
“…These multilaminar membranes have also been observed in pygopodids (Jamieson et al. 1996) and during spermiogenesis in Anolis lineatopus (Rheubert et al. in press) resulting from vesicles originating from the endoplasmic reticula.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These multilaminar membranes have also been observed in pygopodids (Jamieson et al. 1996) and during spermiogenesis in Anolis lineatopus (Rheubert et al. in press) resulting from vesicles originating from the endoplasmic reticula.…”
Section: Discussionmentioning
confidence: 70%
“…These spermatozoa characters along with developmental features during spermiogenesis, which are also gaining much needed attention (Healy and Jamieson 1994; Gribbins et al. 2007, 2010; Rheubert et al. in press), have been considered a rich source of non‐traditional morphological characters that can be utilized in phylogenetic analyses (Jamieson 1991; Newton and Trauth 1992; Jamieson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Squamate spermiogenesis follows the same general steps (acrosome formation, nuclear condensation and elongation, and flagellar development) as all vertebrates (including reptiles: Iguania and Scleroglossa) studied to date 10 , 11 , 16 , 17 with Sceloporus bicanthalis being no exception. However, the addition of new taxa into the accumulating data of sperm morphology reveals new characters and new insights into the steps of sperm development.…”
Section: Discussionmentioning
confidence: 96%
“…Only a handful of studies exist that give complete ultrastructural descriptions of spermiogenesis within the Squamata 9 . These studies have shown both conserved characteristics (i.e., nuclear elongation, acrosome development via Golgi vesicles) as well as unique characters (i.e., rough endoplasmic reticulum involvement in acrosome formation; 10 the absence of manchette microtubules) 11 . With each new study, important insights such as the number of Sertoli cells that are interacting with developing elongating spermatids, 12 become evident during germ cell development.…”
Section: Introductionmentioning
confidence: 99%
“…20 and Scincella lateralis, Inset, ma) is found in all species of reptile studied to date during elongation except in Anolis lineatopus, which lacks a manchette all together. 58 The manchette is thought to aid in the elongation of the nucleus when present and is also represented in almost every mammal and bird. 2,26,56,64,68 The manchette has long been thought to be a major player in the elongation and constriction of the nuclear width during amniote spermiogenesis, 64,66 but the exact mechanism is not known.…”
Section: Germ Cell Cycle and Germ Cell Morphologies During Spermatogementioning
confidence: 99%